Inovasi Media Edukatif dalam Pembelajaran Trigonometri dan Statistika di Sekolah Kejuruan Perbatasan - Seo, Hendro Usa Juniano; Guteres, Ilda; Jagom, Yohanes Ovaritus; Gawa, Maria Gracia Manoe; Lakapu, Meryani (Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to enhance students’ understanding and interest in mathematics, particularly in topics often perceived as difficult—trigonometry and statistics. The activity was conducted at SMKS St. Willibrodus Betun, Malaka Regency, involving six students from Universitas Katolik Widya Mandira (UNWIRA) and Universidade Oriental Timor Lorosa’e (UNITAL) Timor Leste. The implementation method consisted of educational outreach using contextual and participatory approaches, along with inclusive language (Indonesian, Tetum, and English) tailored to the students’ and facilitators’ backgrounds. Trigonometry was taught using a student-designed teaching aid called the "trigonometry wheel" from UNWIRA, while statistics was introduced through an interactive educational gamecard developed by students from UNITAL. The results indicated a significant improvement in student enthusiasm, engagement, and comprehension of mathematical concepts that were previously considered abstract and intimidating. Discussions, observations, and practice questions demonstrated that visual and interactive methods were highly effective in reducing math anxiety. Moreover, the cross-border collaboration enriched the learning experiences of both students and facilitators, while promoting values of tolerance, cooperation, and educational diplomacy in the border region. This initiative proves that innovative learning media and contextual approaches can serve as effective solutions for improving the quality of mathematics education in vocational schools